2015
DOI: 10.1016/j.ejrad.2014.10.021
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic oxygen-enhanced magnetic resonance imaging of the lung in asthma—Initial experience

Abstract: Dynamic OE-MRI is feasible in asthma and sensitive to the severity of disease. The technique provides indices related to regional oxygen delivery, uptake and washout that show good one month reproducibility and intra-observer agreement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 27 publications
2
38
0
Order By: Relevance
“…Several studies have used 2D OE‐MRI with T 1 ‐weighting obtained from inversion‐recovery fast spin echo and Look‐Locker GRE pulse sequences for patients with various pulmonary diseases and have observed differences in relative enhancement associated with disease and disease severity. These studies examined small‐volume measurements or ROIs that often covered only a modest portion of the lungs due to the extended scan times required for 3D coverage using these pulse sequences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have used 2D OE‐MRI with T 1 ‐weighting obtained from inversion‐recovery fast spin echo and Look‐Locker GRE pulse sequences for patients with various pulmonary diseases and have observed differences in relative enhancement associated with disease and disease severity. These studies examined small‐volume measurements or ROIs that often covered only a modest portion of the lungs due to the extended scan times required for 3D coverage using these pulse sequences.…”
Section: Discussionmentioning
confidence: 99%
“…The histogram of the PSE values in the lungs generally has a nonsymmetrical distribution, particularly in the obstructed lungs. Therefore, the median PSE (MPSE) value in the lungs was calculated and used as a global measure from UTE OE‐MRI, as reported in prior OE‐MRI studies …”
Section: Methodsmentioning
confidence: 99%
“…MAGNETIC RESONANCE IMAGING (MRI) of the chest can provide regional assessment of lung ventilation by inhaling oxygen (O 2 ), hyperpolarized noble gases, or fluorinated gas . Oxygen‐enhanced (OE) MRI using a 3D radial ultrashort echo time (UTE) sequence supports quantitative differentiation of diseased vs. healthy lungs using whole lung ventilation defect percent (VDP) .…”
mentioning
confidence: 99%
“…Zhang et al [155] demonstrated that dynamic oxygen-enhanced MRI is sensitive to severity of asthma and enables assessments of regional lung function. In oxygen-weighted HP gas MRI, the gas dose is mixed with pure O 2 immediately prior to inhalation to approximate normoxic concentrations (20% O 2 ).…”
Section: Magnetic Resonance Ventilation/perfusion Imagingmentioning
confidence: 99%